Complications and mortality of non-typhoidal salmonella invasive disease: a global systematic review and meta-analysis. Issue 5 (May 2022) - Marchello, Christian S; Birkhold, Megan; Crump, John A; ,; Martin, Laura B.; Ansah, Michael O.; Breghi, Gianluca; Canals, Rocio; Fiorino, Fabio; Gordon, Melita A.; Kim, Jong-Hoon; Hamaluba, Mainga; et al.
Summary: Background: Non-typhoidal salmonella can cause serious, life-threatening invasive infections involving the bloodstream and other normally sterile sites. We aimed to systematically review the prevalence of complications and case-fatality ratio (CFR) of non-typhoidal salmonella invasive disease to provide contemporary global estimates and inform the development of vaccine and non-vaccine interventions. Methods: We did a global systematic review and meta-analysis of studies investigating the complications and mortality associated with non-typhoidal salmonella invasive disease. We searched Embase, MEDLINE, Web of Science, and PubMed for peer-reviewed, primary research articles published from database inception up to June 4, 2021, with no restrictions on language, country, date, or participant demographics. Only studies reporting the proportion of complications or deaths associated with non-typhoidal salmonella invasive disease, confirmed by culture of samples taken from a normally sterile site (eg, blood or bone marrow) were included. We excluded case reports, case series, policy reports, commentaries, editorials, and conference abstracts. Data on the prevalence of complications and CFR were abstracted. The primary outcomes were to estimate the prevalence of complications and CFR of non-typhoidal salmonella invasive disease. We calculated an overall pooled CFR estimate and pooled CFR stratified by UN region, subregion, age group, and by serovar when available with a random-effects meta-analysis. A risk-of-bias assessment was done, and heterogeneity was assessed with Cochran's Q Test, I 2, and τ 2 . This study was done in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, and is registered with PROSPERO, CRD42020202293. Findings: The systematic review returned a total of 8770 records. After duplicates were removed, 5837 titles and abstracts were screened, yielding 84 studies from 35 countries after exclusions. Of these included studies, 77 (91·7%) were hospital-based and 66 (78·6%) were located in Africa or Asia. Among 55 studies reporting non-typhoidal salmonella disease-associated complications, a total of 45 different complications were reported and 1824 complication events were identified among 6974 study participants. The most prevalent complication was septicaemia, occurring in 171 (57·2%) of 299 participants, followed by anaemia in 580 (47·3%) of 1225 participants. From 81 studies reporting the CFR of non-typhoidal salmonella invasive disease, the overall pooled CFR estimate was 14·7% (95% CI 12·2–17·3). When stratified by UN region, the pooled CFR was 17·1% (13·6–21·0) in Africa, 14·0% (9·4–19·4) in Asia, 9·9% (6·4–14·0) in Europe, and 9·6% (0·0–25·1) in the Americas. Of all 84 studies, 66 (78·6%) had an overall high risk of bias, 18 (21·4%) had a moderate risk, and none had a low risk. Substantial heterogeneity ( I 2 >80%) was observed in most (15 [65·2%] of 23) CFR estimates. Interpretation: Complications were frequent among individuals with non-typhoidal salmonella invasive disease and approximately 15% of patients died. Clinicians, especially in African countries, should be aware of non-typhoidal salmonella invasive disease as a cause of severe febrile illness. Prompt diagnoses and management decisions, including empiric antimicrobial therapy, would improve patient outcomes. Additionally, investments in improving clinical microbiology facilities to identify non-typhoidal salmonella and research efforts towards vaccine development and non-vaccine prevention measures would prevent non-typhoidal salmonella invasive disease-associated illness and death. Funding: EU Horizon 2020 research and innovation programme.